Experimental and analytical investigation on flexural behaviour of glulam-concrete composite beams with interlayer. (June 2021) - Du, Hao; Hu, Xiamin; Han, Guohui; Shi, Danrong
Abstract: In various practical applications of timber-concrete composite (TCC) beams, particularly for the rehabilitation of timber buildings, there is a timber board interlayer at the interface. The timber board is applied as the formwork for the pouring of concrete slab and usually left behind as part of the composite structure. There are few investigations performed on the mechanical behaviour of TCC beams with timber board interlayer. In this paper, two full-scale glulam-concrete composite beams with inclined crossing screws and notched connectors were constructed and loaded by four-point bending to investigate the flexural performance of composite beams with timber board interlayer. Experimental results demonstrated that the failure mechanism of the composite beam was combined bending and tensile failure of the glulam beam. Due to the flexibility of the shear connector, relative slip occurred at the interface and the assumption of a plane section remaining plane did not hold for the composite cross-section as a unit. Additionally, analytical models for the bending stiffness and load-bearing capacity of TCC beams with interlayer were proposed. Comparisons demonstrated that the bending capacity and stiffness of TCC beams with interlayer could be well predicted using the calculation method. Highlights: Experimental researches on the TCC beams with interlayer were conducted. The model for predicting bending stiffness of the TCC beams was proposed. The model for predicting load-bearing capacity of the TCC beams was proposed.